Politik Hukum HAM di Indonesia - Endrik Safudin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2015)
Law was born to provide protection, justice and certainty in every dimension of social and state life, both individuals and groups. In this context, the law provides guarantees and principles of recognition and protection of human rights. This noble goal of the law will be easily realized when the politics of the law is clear. But in reality, the occurrence of human rights violations cannot be denied even though since the beginning the Indonesian state has adhered to the principles of the rule of law and democracy. Cases of human rights violations in the past are debts that must be resolved. Therefore, one of the problems today is how to resolve cases of human rights violations that occurred in the past and how to prepare more responsive legal instruments so that in the future human rights violations, especially those committed by the state, can be avoided. Furthermore, the resolution of past human rights violations is the key to upholding human rights in Indonesia in the future. This is where the political meaning of human rights law in Indonesia is to design more responsive legal regulations. Therefore, to create a more responsive politics of human rights law in Indonesia, we must first examine the journey of human rights in Indonesia through historical research. This is because historical research can reveal how the concept of human rights has been made in the past and how the concept of human rights should be made to build a better future. For this reason, a high commitment is needed from the government to develop the politics of human rights law in Indonesia.